IC 7998 Research And Technologic Work On Explosives, Explosions, And Flames: Fiscal Years 1955 And 1956 ? Summary And Introduction - Ruth F. Brinkley (The National Institute for Occupational Safety and Health (NIOSH), 1961)
This report is the 17th of a series originally issued annually, and more recently bienially, to acquaint the reader with the work of the Division of Explosives Technology, Federal Bureau of Mines. It differs from preceding reports in that its material is presented in two parts: Part I reviews briefly the overall activities of the Division during fiscal years 1955 and 1956;4/ part II presents in abstract form, the publications of the Division during that period. As it is not unusual for research completed in the course of one report period to be published only in the following period, the Bureau believes that the present approach will give a more accurate presentation of its work for the period considered. The Bureau hopes too, that the somewhat more concise presentation will prove convenient to the reader.5/ PART I -RESEARCH AND TECHNOLOGIC ACTIVITIES The activities of the Division during fiscal years 1955 and 1956 reflected the steadily growing preoccupation with factors affecting the safety of permissible explosives and those affecting the tests used for approval of these explosives. Findings by a team of French investigators prompted a study of the influence of atmospheric moisture on the ignition of firedamp by